Desempenho agronômico de genótipos em cana-soca no brejo paraibano, oriundos a partir de micropropagação - Cruz, Manoela Gomes da (2022)
Sugarcane is considered a great alternative for the biofuel sector, due to the potential for producing ethanol and various products. Thus, genetic improvement becomes a great option, allowing the development of the best varieties that adapt to environmental adversities. Thus, the objective was to evaluate the agronomic performance of nine sugarcane products, derived from micropropagation, in Brejo Paraibano, analyzing them as productive and constructive characteristics. The research was conducted at the Experimental Farm Chã de Jardim, belonging to the Federal University of Paraíba, in the municipality of Areia-PB. Its conduction and evaluations were carried out from August 2020, in which the second-year ratoon cane began. The design was in randomized blocks (DBC), with four replications and nine treatments, totaling 36 plots. The treatments applied were nine sugarcane genotypes, originated from vegetative micropropagation, namely: CTC 15, CTC 9004, CTC 9005, RB 015935, RB 965902, RB 975201, RB 975242, RB 935744 and RB 867515 as a control. 05 plants were demarcated in the central lines of each plot, for evaluations every 60 days, totaling 06 evaluations. The evaluations were to determine plant height, number of plants per meter, number of open leaves, number of internodes, diameter of stems, length of leaves, width of leaves, Brix and productivity. The data were submitted to analysis of variance by the F test and the means were compared by the Tukey test at the 5% probability level. Quantitative data were submitted to regression analysis using Sisvar software. It was found that the genotypes RB 867515 and RB 975201 stood out with the highest average plant height, with respective heights of 139.97 cm and 135.17 cm. As for the number of plants per meter, the superiority was obtained with the genotypes RB 935744, RB 975242, CTC 9005, CTC 9004 and CTC 15, which were statistically equal, with averages of 11.18 plants, 9.99 plants, 10 .15 plants, 9.56 plants and 9.79 plants, respectively. Sugarcane genotypes did not differ in terms of number of plants per meter when they reached 60 days, 220 days, 270 days, 310 days and 390 days after harvest. As for the number of internodes, it can be observed that the genotypes differed in this variable from 220 days until the end of the cycle at 390 days after harvest. At 220 days, the genotypes RB 975201 and CTC 9005 showed more numbers of internodes, with averages of 10.15 internodes and 10.45 internodes per plant, respectively. The productivity and maturation index did not differ between the genotypes studied. The genotypes RB 867515, RB 935744, RB 975201 and CTC 9004 show the best structural developmental characteristics.